Analisis Faktor yang Mempengaruhi Investasi di Indonesia Tahun 1990-2010: Metode ECM - Sarungu, J.J; Endah K, Maharsi (Jurnal Ekonomi Kuantitatif Terapan, 2013)
Investment is important for the economy of a country because it serves as a key to economic growth. Investment will increase the productivity of economic activity, increase employment opportunities and expanding markets. This research has a purpose determine the factors that influence investment in Indonesia in 1990-2010. This study uses Error Correction Model (ECM). The analysis showed that variable interest rate affect investment negatively and significantly to the amount of investment in the short term and long term, the inflation variable is negative and significant effect on the amount of investment in the long term and variable rate has a positive and significant impact on the amount of investment in the long term.
Keywords: Investasi; Suku Bunga Kredit Investasi; Inflasi; Kurs; Error Correction Model (ECM)